2009
DOI: 10.2169/internalmedicine.48.1560
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Intimal Sarcoma of the Pulmonary Artery Treated with Chemoradiotherapy

Abstract: We report on a 45-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Only surgical resection prolongs survival times (2,3). The effectiveness of radiation therapy and chemotherapy remains controversial although some studies have reported that both therapies may be effective (5)(6)(7). The use of these therapies after surgical treatment has been found to prolong survival time compared with surgery alone (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only surgical resection prolongs survival times (2,3). The effectiveness of radiation therapy and chemotherapy remains controversial although some studies have reported that both therapies may be effective (5)(6)(7). The use of these therapies after surgical treatment has been found to prolong survival time compared with surgery alone (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, no standard regimens for the use of these chemotherapeutic agents have been established. Some reports have shown a potential usefulness for radiation therapy (7,20). Considering the side effects of chemotherapy, including bone marrow suppression, we first selected radiation therapy to prevent tumor recurrence in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preoperative severity of right heart failure seemstobeapredictorforpatientoutcome.Theroleofneoadjuvant or adjuvant chemotherapy or radiation treatment strategies needs to be evaluated. Some reports have shown beneficial effects [7,[11][12][13]. Anthracycline-and ifosfamidebased chemotherapies are available options [7].…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…However, in isolated cases chemotherapy or radiotherapy seems to be effective against pulmonary artery sarcoma [3,8,12]. Adjuvant radiochemotherapy after surgical treatment seems to be superior to surgery alone [4], from a retrospective point of view.…”
mentioning
confidence: 99%